Rising Healthcare Costs and Utilization among Young Adults with Cirrhosis in Ontario: A Population-Based Study - Jeffrey B. Ames; Maya Djerboua; Norah A. Terrault; Christopher M. Booth; Jennifer A. Flemming (Canadian Journal of Gastroenterology and Hepatology)
Objectives. Chronic diseases account for the majority of healthcare spending. Cirrhosis is a chronic disease whose burden is rising, especially in young adults. This study aimed at describing the direct healthcare costs and utilization in young adults with cirrhosis compared to other chronic diseases common to this age group. Methods. Retrospective population-based study of routinely collected healthcare data from Ontario for the fiscal years 2007–2016 and housed at ICES. Young adults (aged 18–40 years) with cirrhosis, inflammatory bowel disease (IBD), and asthma were identified based on validated case definitions. Total and annual direct healthcare costs and utilization were calculated per individual across multiple healthcare settings and compared based on the type of chronic disease. For cirrhosis, the results were further stratified by etiology and decompensation status. Results. Total direct healthcare spending from 2007 to 2016 increased by 84% for cirrhosis, 50% for IBD, and 41% for asthma. On a per-patient basis, annual costs were the highest for cirrhosis ($6,581/year) compared to IBD ($5,260/year), and asthma ($2,934/year) driven by acute care in cirrhosis and asthma, and drug costs in IBD. Annual costs were four-fold higher in patients with decompensated versus compensated cirrhosis ($20,651/year vs. $5,280/year). Patients with cirrhosis had greater use of both ICU and mental health services. Conclusion. Healthcare costs in young adults with cirrhosis are rising and driven by the use of acute care. Strategies to prevent the development of cirrhosis and to coordinate healthcare in this population through the development of chronic disease prevention and management strategies are urgently needed.